Mean muscle attenuation correlates with severe acute pancreatitis unlike visceral adipose tissue and subcutaneous adipose tissue. Issue 10 (1st December 2019) - Sternby, Hanna; Mahle, Mariella; Linder, Nicolas; Erichson-Kirst, Laureen; Verdonk, Robert C; Dimova, Alexandra; Ignatavicius, Povilas; Ilzarbe, Lucas; Koiva, Peeter; Penttilä, Anne; Regnér, Sara; Bollen, Thomas L; et al.
Abstract : Background: Acute pancreatitis (AP) is a frequent disorder with considerable morbidity and mortality. Obesity has previously been reported to influence disease severity. Objective: The aim of this study was to investigate the association of adipose and muscle parameters with the severity grade of AP. Methods: In total 454 patients were recruited. The first contrast‐enhanced computed tomography of each patient was reviewed for adipose and muscle tissue parameters at L3 level. Associations with disease severity were analysed through logistic regression analysis. The predictive capacity of the parameters was investigated using receiver operating characteristic (ROC) curves. Results: No distinct variation was found between the AP severity groups in either adipose tissue parameters (visceral adipose tissue and subcutaneous adipose tissue) or visceral muscle ratio. However, muscle mass and mean muscle attenuation differed significantly with p ‐values of 0.037 and 0.003 respectively. In multivariate analysis, low muscle attenuation was associated with severe AP with an odds ratio of 4.09 (95% confidence intervals: 1.61–10.36, p ‐value 0.003). No body parameter presented sufficient predictive capability in ROC‐curve analysis. Conclusions: Our results demonstrate that a low muscle attenuation level is associated with an increased risk of severe AP. Future prospective studies will help identify the underlying mechanisms and characterise the influence of body composition parameters on AP.